Satire politique et sociale dans les opérettes de Gilbert et Sullivan - Anita Cornic (Revue LISA)
Although Gilbert and Sullivan’s Operas were first and foremost light, humorous works devised to entertain their mostly middle-class audience, they are characterised by a certain amount of political and social satire, as this paper aims to show through telling examples. Beyond the merry and pleasant songs which remain part and parcel of the English cultural heritage, the shafts directed against the social and political institutions (especially the House of Lords and the class system) have lost none of their piquancy and even relevance for today’s audience.